“I always feel like I’m the first deaf person they have ever met:” Deaf Awareness, Accessibility and Communication in the United Kingdom’s National Health Service (NHS): How can we do better? - Bhavisha Parmar; Helen Henshaw; Shahad Howe; Ann Marie Dickinson; Crystal Rolfe; Philip Le Mere; Emmanuelle Blondiaux-Ding; Zara Musker; Rachel Stevenson; Sarah E. Hughes; Sian Calvert; Emma Stapleton; et al. (PLoS ONE, 2025)
Background Barriers to communication significantly reduce access to health services for people with deafness or hearing loss (PDHL). These barriers contribute to reduced healthcare-seeking behaviour, poorer access to health information, and adverse health outcomes. In response, a multidisciplinary working group of patients, clinicians, researchers, and charity representatives was established to investigate accessibility, communication, and deaf awareness within the United Kingdom’s (UK) National Health Service (NHS). Methodology A cross-sectional survey was conducted to explore the communication and accessibility experiences of PDHL NHS patients, and their perceived impact on well-being. The survey used rating scales and open-ended questions and data were analysed using descriptive statistics and thematic analysis. The survey was made available in British Sign Language (BSL). Results The online survey was completed by 556 PDHL, including 50 parents, carers, or family members who had accompanied PDHL friends or relatives to NHS appointments. All respondents had used NHS services within the last 24 months, with 10% identifying BSL as their preferred language. Qualitative analysis of the open-ended responses generated three key themes: 1) Accessibility challenges, 2) Impact of communication difficulties across the service pathway, and 3) Lack of consistent, effective deaf-aware communication. Overall, 64.4% of PDHL NHS patients reported missing 50% or more of the important information provided during their NHS appointments, and 32% were satisfied with the communication skills of healthcare staff. Conclusion This study presents the largest UK-wide dataset of its kind, and findings highlight the widespread non-compliance with the legally mandated Accessible Information Standards (AIS) within NHS services. The communication barriers identified in this study have significant and long-term implications for the well-being of PDHL patients. Utilising these findings, our working group has developed a set of ‘Recommendations For Change’ to improve deaf awareness and effective communication across the NHS.